Optimization Of Chicken Feather Waste Into High-Protein Chicken Feather Meal - Fitriana, Wiwit Denny; Novitasari, Afsah; Qomariana, Anna; Anugrah, Chandra Sukma; Islami, Mohamad Fajril (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This study aims to process chicken feather waste into high-protein feather meal using a completely randomized design (CRD) experimental model. Four processing methods were applied: physical (P1), chemical with 12% HCl (P2), enzymatic with 0.4% proteolytic enzyme (P3), and chemical with 6% NaOH (P4). Proximate analysis included crude fiber, protein, moisture, ash, and fat content. An organoleptic test evaluated the color, texture, and odor of the meal. ANOVA and DMRT at the 5% level indicated significant differences between methods. The chemical method with 6% NaOH yielded the highest protein content (50.1%). Organoleptic data showed that all samples had similar sensory characteristics. The study concludes that the chemical processing method with 6% NaOH is the most effective in enhancing protein content, providing an optimal solution for economically and environmentally utilizing chicken feather waste.